2011
DOI: 10.3892/or.2011.1181
|View full text |Cite
|
Sign up to set email alerts
|

The cell adhesion molecule L1 promotes gallbladder carcinoma progression in vitro and in vivo

Abstract: Abstract. Recent studies have demonstrated that the cell adhesion molecule, L1, is expressed in several malignant tumor types and its expression correlates with tumor progression and metastasis. However, the role of L1 in gallbladder carcinoma (GBC) remains unclear. Here, we demonstrate that L1 is expressed in GBC cells and plays an important role in the growth, motility, invasiveness, and adhesiveness of GBC cells. Specific depletion or overexpression of L1 in the GBC cell lines JCRB1033 and SNU-308, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Given that both GAS6 and L1CAM have been linked to Akt signalling2728, and that TWIST2-mediated activation of Akt has been previously implicated in acquired cisplatin resistance22, we hypothesized that Akt may also be a key factor downstream from TWIST1, GAS6, and L1CAM . We also hypothesized that knockdown of GAS6 or L1CAM in TWIST1 overexpressing cells could inhibit upregulation and activation of Akt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that both GAS6 and L1CAM have been linked to Akt signalling2728, and that TWIST2-mediated activation of Akt has been previously implicated in acquired cisplatin resistance22, we hypothesized that Akt may also be a key factor downstream from TWIST1, GAS6, and L1CAM . We also hypothesized that knockdown of GAS6 or L1CAM in TWIST1 overexpressing cells could inhibit upregulation and activation of Akt.…”
Section: Resultsmentioning
confidence: 99%
“…It was found to be an indicator of poor survival in endometrial carcinoma and correlated with progression, stage, grade, and poor survival in ovarian cancer4344. Finally, like GAS6, L1CAM has been shown to signal through the PI3K/Akt pathway, and drives progression and invasion in gallbladder carcinoma28. We therefore examined whether knockdown of GAS6 or L1CAM would impact cisplatin treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The differential effects of L1CAM knockdown in these two cell lines may represent that L1CAM signaling pathway in the TFK-1 cells is different from that in EGI-1 cells. In fact, we previously observed that L1CAM overexpression in gallbladder carcinoma SNU308 or ICC cells with wild type KRAS increased cell proliferation, migration and invasion through activation of FAK and AKT signaling (Jung et al, 2011; Min et al, 2010). To elucidate the functional role of L1CAM in the ECC cells with wild type KRAS , the effect of L1CAM overexpression in TFK-1 cells needs to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…L1CAM was originally identified as a neural cell adhesion molecule that plays an essential role in the development of the nervous system (Grumet and Edelman, 1988). Subsequently, L1CAM has been found to be aberrantly expressed in a variety of malignant tumors, including ovarian cancer, melanoma, breast cancer, gastric cancer, colorectal cancer, non-small cell lung cancer, pancreatic cancer, neuroblastoma, and cholangiocarcinoma, and its expression correlates with a poor prognosis and metastasis (Altevogt et al, 2016; Chen et al, 2013; Jung et al, 2011; Li et al, 2009; Min et al, 2010; Samatov et al, 2016; Weidle et al, 2009). Studies on the cellular functions of L1CAM have demonstrated its promotion of cellular proliferation, migration, invasion, and chemoresistance (Kiefel et al, 2012; Raveh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-L1CAM mAb has displayed therapeutic activity in a mouse model for ovarian carcinoma (Arlt et al, 2006; Wolterink et al, 2010). Previously, we found that L1CAM is involved in tumor progression of ICC, ECC, and gallbladder carcinoma; we generated a murine mAb, A10-A3 (IgG1) binding to the Ig1 domain of L1CAM (Li et al, 2009; Min et al, 2010; Choi et al, 2011; Jung et al, 2011; Wei et al, 2011). In the present study, we constructed the cA10-A3 containing the constant regions of human IgG1, confirmed its ADCC activity in vitro , and evaluated its therapeutic activity in a Choi-CK xenograft model.…”
Section: Discussionmentioning
confidence: 99%